Mythology : timeless tales of Gods and heroes - Hamilton, Edith, 1867-1963 (New York, N.Y. : Grand Central Publishing, 2011)
A collection of Greek and Roman myths from various classical sources arranged in section on the gods and early heroes, love and adventure stories, heroes before and during the Trojan War, and lesser myths. Includes a brief section on Norse mythology
Includes index
Accelerated Reader AR
Keywords: Geographical myths; Mythology